HEART RATE VARIABILITY, VENTRICULAR LATE POTENTIALS AND HEART RATE TURBULENCE AS INDICATORS OF CORONARY REPERFUSION IN ST SEGMENT ELEVATION MYOCARDIAL INFARCTION - E. A. Shigotarova; E. V. Dushina; V. A. Galimskaya; V. E. Oleynikov (Столичная издательская компания, 2017)
Aim. To evaluate the dynamics of the parameters of autonomic balance and electrical instability of the myocardium depending on the effectiveness of the restoration of coronary blood flow in pharmacoinvasive revascularization in patients with acute ST segment elevation myocardial infarction.Material and methods. The study included 91 patients who underwent effective thrombolytic therapy (TLT) according to the ECG criteria, followed by (3-24 hour later) coronary angiography with percutaneous coronary intervention (PCI). Before and after PCI the telemetric ECG recording was conducted. The dynamics of the temporal and spectral characteristics of heart rate variability (HRV), presence of ventricular late potentials (VLP) and abnormal heart rate turbulence (HRT) were evaluated.Results. The episodes of ST-segment re-elevation by1 mm or more, lasting at least 1 min, and the dynamics of some HRV indices indicated the development of rethrombosis after TLT. The increase in the mean square deviation of normal intervals to 82.5 (64.5; 94) ms, the average value of the standard deviations of normal intervals calculated over 5-minute intervals throughout the entire recording to 37.5 (31.5; 47.5) ms, the total power of the spectrum and the power of high frequency waves, as well as the decrease in the power of ultra-low frequency waves were found after PCI in the group with a rethrombosis of the infarct-related coronary artery. The analysis of VLP in this group showed an increase in duration of the filtered QRS complex after TLT (to 128.7±34.5 ms), and the root mean square value of the last 40 ms of the QRS complex after PCI (to 49±50.3 μV).Pathological deviations of the HRT parameters (especially the onset of turbulence) independently on the absolute values were registered more often in patients with rethrombosis, and abnormal values of both HRT parameters were found only in patients with episodes of unstable coronary blood flow.Conclusion. The results are the indirect evidences of disruption of autonomic regulation of cardiac activity and increased arrhythmic readiness of myocardium in developing rethrombosis of coronary artery. The pronounced reperfusion injury of the myocardium evidently plays an important role in this process and is associated with embolization of the vessels of the microcirculatory bed, release of free radicals and alteration of cardiomyocytes, especially due to prolonged ischemia.